EUPATI Guidance for Patient Involvement in Medicines Research and Development (R&D); Guidance for Pharmaceutical Industry-Led Medicines R&D - Warner, Kay; See, Wolf; Haerry, David; Klingmann, Ingrid; Hunter, Amy; May, Matthew (Frontiers in Medicine, 2018)
Integration of patients into the medicines development process needs to be structured and governed by clear rules and modes of operation to be effective and yield the best results for all stakeholders. Existing codes of practice for patient involvement with various stakeholders do not comprehensively cover the full scope of R&D, with the exception of more general statements applicable to interaction. Overarching guidance on meaningful and ethical interaction is missing. The EUPATI guidance document for patient involvement in industry-led medicines research and development covers the interaction between patients and the pharmaceutical industry within all functions throughout the medicines R&D lifecycle in relation to medicines for human use. It relates to activities pre-approval and post marketing, involving individuals and groups of patients.